2001
DOI: 10.1136/jnnp.70.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal and thalamic neurostimulation in severe tardive dystonia

Abstract: A 70 year old woman presented with a 6 year history of medically refractory severe tardive dystonia. After informed consent, a bilateral stereotactic electrode placement targeting the ventral intermediate thalamic nucleus (VIM) and the globus pallidus internus (GPi) was performed. After bilateral stimulation of the GPi, the patient showed a clear and stable improvement of the painful dystonic syndrome within hours. Stimulation of the VIM did not improve the hyperkinetic movements and simultaneous stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 15 publications
3
94
0
1
Order By: Relevance
“…9 The thalamic anatomy has many descriptions that could lead to targeting changes, and the fact that it has unclear and overlapped nuclear borders interferes with the clinical analysis. Even changes inside a thalamic nucleus can have a different effect; for example, the posteromedial part of the Vim can treat tremor and drug-induced dyskinesias, and the anterolateral part can only treat tremor, 22 which can also be explained by stimulation of a nearby nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 The thalamic anatomy has many descriptions that could lead to targeting changes, and the fact that it has unclear and overlapped nuclear borders interferes with the clinical analysis. Even changes inside a thalamic nucleus can have a different effect; for example, the posteromedial part of the Vim can treat tremor and drug-induced dyskinesias, and the anterolateral part can only treat tremor, 22 which can also be explained by stimulation of a nearby nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Final programming was in the GPi: 450 μsec, 130 Hz, 1.0 V; and in the ventral oral complex: 60 μsec, 130 Hz, 3.0 V. Other studies did not find benefits with thalamic stimulation. 17,22,24 In a retrospective evaluation of 19 patients, Vercueil et al 24 found that those treated with GPi DBS had a better outcome, and 3 patients in the thalamic group had rescue GPi DBS, with subsequent improvement. One hemidystonic patient lost thalamic stimulation benefits; this individual had a greater response with pallidal stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several case reports indicated that GPi DBS was effective in focal segmental dystonia involved in neck, facial, trunk, upper and lower limbs [44][45][46][47][48][49][50]. Interestingly, the combined targets of ventral intermediate nucleus (Vim) plus GPi DBS significantly improved Myoclonus Dystonia, a rare form of movement disorder with epsilon-sarcoglycan gene mutations and prominent action myoclonus plus dystonia [51].…”
Section: Optimal Target Selectionmentioning
confidence: 99%